Estudio sobre las principales variables del sistema de pensiones en Colombia en el periodo 1992-2023 utilizando distribuciones de probabilidad (2024)
The “Study on the main variables of the pension system in Colombia in the Period 1992-2023” focuses on analyzing the main variables of the pension system in Colombia using probability distributions. This analysis presents the theory necessary to understand the fit of probabilistic models to the information of the pension system in Colombia, uses goodness-of-fit measures in different probabilistic models to determine the best model that fits the data, and graphically illustrates the function density, the cumulative distribution function of the studied models and the goodness-of-fit results. To this end, the study presents a diagnosis of the current situation of the pension system in Colombia, the regulatory framework of the Colombian pension system, the pension regimes, and a comparison between the two predominant regimes in Colombia. In addition, a characterization of the current state of the main variables of the pension system in Colombia is presented. Subsequently, it presents the theoretical framework of the probability distributions, and using the R Software, it performs a distribution adjustment to the data of the three main variables of the system under study.